2003
DOI: 10.1080/01902140303789
|View full text |Cite
|
Sign up to set email alerts
|

Different Proliferative Capacity of Lung Fibroblasts Obtained From Control Subjects and Patients With Emphysema

Abstract: To characterize the possible role of a dysregulated proliferative capacity of pulmonary fibroblasts in insufficient tissue repair in lungs from patients with pulmonary emphysema, the authors undertook in vitro proliferative studies with pulmonary fibroblasts obtained from lung tissue of patients with emphysema. A comparison was made with fibroblasts from control subjects. The authors determined the in vitro proliferative capacity of fibroblasts at basal culture conditions and after modulation with interleukin-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
39
0

Year Published

2006
2006
2014
2014

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 38 publications
(39 citation statements)
references
References 21 publications
(25 reference statements)
0
39
0
Order By: Relevance
“…In line with this, lung fibroblasts from patients with emphysema exhibit a reduced proliferation rate, lower number of population doublings in serial passaging (Holz et al 2004), and altered growth factor response (Holz et al 2004;Noordhoek et al 2003). In addition, we found an increased staining for senescence-associated beta-galactosidase (β-gal, (Dimri et al 1995)), as well as increased mRNA expression of the insulin-like growth factor-binding proteins (IGFBP)-3 and -rP1 in these cells (Müller et al 2006).…”
Section: Introductionmentioning
confidence: 60%
“…In line with this, lung fibroblasts from patients with emphysema exhibit a reduced proliferation rate, lower number of population doublings in serial passaging (Holz et al 2004), and altered growth factor response (Holz et al 2004;Noordhoek et al 2003). In addition, we found an increased staining for senescence-associated beta-galactosidase (β-gal, (Dimri et al 1995)), as well as increased mRNA expression of the insulin-like growth factor-binding proteins (IGFBP)-3 and -rP1 in these cells (Müller et al 2006).…”
Section: Introductionmentioning
confidence: 60%
“…BUCKLEY et al [18] suggested that this chronic inflammation occurs because of disordered fibroblast behaviour, which leads to inappropriate survival and retention of leukocytes within inflamed tissue [38]. Thus it is not surprising that fibroblasts in COPD tissue show a functionally altered behaviour under the influence of the local cytokine microenvironment [11,18]. The differentially expressed adhesion-related genes found in GOLD stage IV COPD fibroblasts when stimulated with CD8 supernatant supports the theory of a prominent role of fibroblasts in the chronic inflammatory process observed in COPD.…”
Section: Discussionmentioning
confidence: 99%
“…Absence of mycoplasma contamination in the fibroblast cultures was confirmed with a mycoplasma detection kit (Roche Diagnostics, Almere, the Netherlands). Isolated cells were characterised as fibroblasts by morphological appearance and expression pattern of specific proteins [11]. All cells exhibited a characteristic staining pattern for vimentin, fibronectin, and the fibroblast marker prolyl-4-hydroxylase and lacked immunoreactivity for keratin.…”
Section: Subjectsmentioning
confidence: 99%
See 2 more Smart Citations